Connecting values to action : non-corporeal actants and choice - Hartt, Christopher M. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Why do we make the decisions we do? And how can we understand what influences our decisions? Non-Corporeal Actant Theory explores decisions and outcomes through the perspective of values, beliefs, ideas, and concepts - all integral parts of our everyday lives and the actor-networks that we take part in as decision-makers. Connecting Values to Action: Non-Corporeal Actants and Choice brings together a cast of expert contributors to delve into this theory and its ramifications for our lives. With chapters that analyze decisions made by death-defying free climbers, indigenous people facing the loss of their culture, and corporates responding to the #MeToo movement, editor Christopher M. Hartt examines how decisions are affected by the widening range of actor-networks that come with social media and technological development.For anyone struggling to understand how a decision is made, Connecting Values to Action offers a pathway to finding the causes of that decision. Exploring the role of non-corporeal actants on the very real consequences of decisions, this is an unmissable book for students and researchers of management and decision-making.
Includes index.
Keywords: Decision making; Leadership; Business & Economics -- Decision-Making & Problem Solving; Management decision making